Contribution of Histamine to Nociceptive Behaviors Induced by Intrathecally Administered Cholecystokinin-8 - Hayashi, Takafumi; Watanabe, Chizuko; Katsuyama, Soh; Agatsuma, Yasuyuki; Scuteri, Damiana; Bagetta, Giacinto; Sakurada, Tsukasa; Sakurada, Shinobu (Frontiers in Pharmacology, 2020)
The involvement of spinal release of histamine in the nociceptive behaviors induced by cholecystokinin-8 (CCK-8) was investigated in mice. Intrathecal (i.t.) injection of CCK-8 elicited the nociceptive behaviors consisting of scratching, biting, and licking. The nociceptive behaviors induced by i.t. treatment with CCK-8 showed two bell-shaped patterns. The histamine H3 receptor antagonist significantly promoted the nociceptive behaviors induced by CCK-8 at doses of 1–100 fmol and 100 pmol. The nociceptive behaviors elicited by CCK-8 was inhibited by i.t. administration of the CCK-B receptor antagonist in a dose-dependent manner, but not by the CCK-A receptor antagonist. The nociceptive behaviors induced by CCK-8 were markedly suppressed by i.t. pretreatment with antiserum against histamine and were abolished in histidine decarboxylase-deficient mice. In histamine H1 receptor-deficient mice, the nociceptive behaviors induced at both 10 amol and 10 pmol of CCK-8 were not affected. The tachykinin neurokinin-1 (NK1) receptor antagonists inhibited CCK-8 (10 pmol)-induced nociceptive behaviors in a dose-dependent manner. No significant reduction in CCK-8 (10 amol)-induced nociceptive behaviors was detected after co-administration of the tachykinin NK1 receptor antagonists. The nociceptive behaviors elicited by CCK-8 were inhibited by i.t. administration of the antagonist for the N-methyl-D-aspartate (NMDA) receptor in a dose-dependent manner. Our results suggest that the nociceptive behaviors induced by i.t. administration of CCK-8 (10 pmol) are mediated through the spinal release of histamine and are elicited via activation of the tachykinin NK1 and NMDA receptors, whereas the nociceptive behaviors induced by i.t. administration of CCK-8 (10 amol) are mediated through the spinal release of histamine and elicited via NMDA receptor activation.